Comparison of three-port versus four-port laparoscopic cholecystectomy - Azad Kumar; Surya Prakash; Rajkumar Verma (Asian Journal of Medical Sciences, 2024)
Background: In the era of laparoscopic surgery, early recovery and less post-operative pain are major goals to improve patient care and cut down cost. Several studies have demonstrated less post-operative pain and early recovery with the reduction in size and number of ports. Aims and Objectives: To compare three-port laparoscopic cholecystectomy (LC) with four-port LC in chronic calculous cholecystitis patients. We compared the feasibility of the procedure, total operative time, intraoperative difficulties, post-operative pain, incidence of complications, and cosmetic results. Materials and Methods: The study was done in Maharani Laxmi Bal Medical College, Jhansi, between April 2021 and November 2022, including 2 groups of patients (Group A-50 patients of three-port LC and Group B-50 patients of four-port LC). Results: Most of the participants were from 18 to 30 years (32%, 38%) and 31 to 40 years (30%, 12%) in both the groups. The mean duration of surgery in three-port and four-port group was 41.64±6.972 and 42.22±13.784 min, respectively (p=0.79). Hospital stay was three-port and four-port group was 3.33±0.789 and 3.86±0.707 days, respectively (p=0.0001). 100 patients were included, with 2085 patients. The mean age of the studied patients was 46.38 years with female preponderance. The mean operative time for three ports was 66.90 min and for four ports, it was 75.45 min. The mean duration of post-operative stay for three-port was 4.66, and for the conventional group, it was 5.30. Conclusion: Three-port lap cholecystectomy can be advocated to be better than the 4-port technique, but especially in experienced hands, and 4-port LC is better for beginners.